Evidence use and advocacy coalitions: Intermediary organizations and philanthropies in Denver, Colorado - Scott, Janelle; Jabbar, Huriya; Goel, Priya; DeBray, Elizabeth; Lubienski, Christopher (Education Policy Analysis Archives, 2015)
The increasing involvement of philanthropists in education policy has contributed to the emergence of a dynamic sector of intermediary organizations (IOs), entities that serve a number of functions in school reform, including advocacy, consultation, policy design, alternative teacher and leadership preparation, and research. In recent years, many IOs have converged into coalitions that are pushing for incentivist educational policies like “parent trigger” laws, charter schools, vouchers, and teacher merit pay or sanctions often tied to value added metrics of teacher performance. This article draws on data from a mixed-methods, multiyear study of research use and dissemination. In this article, we examine the role of foundations in a broader advocacy coalition in Denver, Colorado, a key site for various incentivist reforms, including teacher pay-for-performance and charter schools. We find that IOs and their affiliated networks broker the production and use of research evidence, often targeting government and education policymakers, journalists, and increasingly, influential bloggers and social media communities. This brokering function positions foundations as the “hub” of research production, promotion, and utilization.